The Effect of Extension and Intensification Regional Tax on Receipt Regional Original Income in The Agency Regional Income Management Sumedang District - Tita Kartika; Solihin Royani; Tiana Fenny Krisdina; Annisa Oktavianty Dewi (Jurnal Riset Bisnis dan Investasi, 2026)
This research aims to assess the impact of tax extensification and intensification policies on the optimization of local tax revenues, with a case study at the Regional Revenue Agency (BAPPENDA) of Sumedang Regency. This study adopts a quantitative descriptive design utilizing a survey method involving tax officials from the Regional Revenue Agency (BAPPENDA) of Sumedang Regency. The sample was selected using a purposive sampling technique, where participantswere chosen based on predefined criteria. Data were obtained from both primary and secondary sources, with the primarydata collected through questionnaires distributed to 30 respondents. The instrument used a Likert scale ranging from 1 to 5 to measure responses. Analytical methods applied included normality tests, multiple linear regression, Pearson’s product-moment correlation, coefficient of determination, and hypothesis testing using t-tests and F-tests, conducted with IBM SPSS version 25.The findings reveal that tax extensification exerts a positive but statistically insignificant impact on local tax revenue, indicated by a regression coefficient of 0.223, a t-value of 1.928 (less than the critical value of 2.052),and a significance level of 0.064, exceeding the standard threshold of 0.05. Similarly, tax intensification also demonstrates a positive yet insignificant influence, with a regression coefficient of 0.061, a t-value of 0.377, and a significance level of 0.709, all failing to meet statistical significance. Furthermore, the combined effect of both tax extensification and intensification on local tax revenue is also not statistically significant, as reflected by an F-value of 1.946 (below the critical F-value of 3.09) and a significance level of 0.162, which is higher than 0.05.